2015
DOI: 10.1136/jclinpath-2014-202799
|View full text |Cite
|
Sign up to set email alerts
|

False negative rate for intraoperative sentinel lymph node frozen section in patients with breast cancer: a retrospective analysis of patients in a single Asian institution

Abstract: FNRin our institution is acceptable when compared to other large centres. Failure to detect metastasis in frozen section in more than half of our patients was due to ITCs and micrometastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 31 publications
(17 reference statements)
2
29
0
1
Order By: Relevance
“…After lymph node removal, surgeons must wait for the immunohistochemical analysis (IHA) results to decide if axillary lymph node dissection is necessary, which usually takes 30-60 min. In some cases, a second operation cannot be avoided because the specificity of frozen section rapid pathologic examination cannot reach 100% and the false negative rate is at least 4% [36]. Isabelle et al first used Raman spectra and infrared images to detect the lymph node excision during head and neck tumor surgeries [37] and showed that lymph nodes with metastatic cancer have greater nucleic acid and less lipid and carbohydrate content than normal lymph nodes.…”
Section: Raman Spectroscopy In Tissuesmentioning
confidence: 99%
“…After lymph node removal, surgeons must wait for the immunohistochemical analysis (IHA) results to decide if axillary lymph node dissection is necessary, which usually takes 30-60 min. In some cases, a second operation cannot be avoided because the specificity of frozen section rapid pathologic examination cannot reach 100% and the false negative rate is at least 4% [36]. Isabelle et al first used Raman spectra and infrared images to detect the lymph node excision during head and neck tumor surgeries [37] and showed that lymph nodes with metastatic cancer have greater nucleic acid and less lipid and carbohydrate content than normal lymph nodes.…”
Section: Raman Spectroscopy In Tissuesmentioning
confidence: 99%
“…The use of FS is accompanied with many drawbacks such as considerable waiting time, tissue loss, and cost. Furthermore, false-negative rates are always a concern 8. Intraoperative imprint cytology (IC) has also been suggested as a less expensive and equally accurate alternative to FS; this technique can also be performed on lymph nodes replaced by fat 9,10.…”
Section: Introductionmentioning
confidence: 99%
“…В Сингапурской больнице общего профиля Вонгом и др. был проведен ретроспективный анализ 2202 биопсий СЛУ из 2174 больных раком молочной железы, в течение 7 лет, результаты данного исследования подтвердили взаимосвязь между размером метастаза СЛУ и риском ложноотрицательных заключений после замораживания ткани ЛУ [18]. Они определили общую частоту ложноотрицательных заключений -13,5%, частота же ложноотрицательных заключений при макрометастазах была значительно ниже, и составила всего 3,1%.…”
Section: интраоперационная оценка сигнальных лимфатических узлов (слу)unclassified